Efficacy of two intensive decontamination protocols and their effects after 30 days on environmental contamination by cyclophosphamide - Delafoy Clémence; Chabut Claire; Tanguay Cynthia; Bussières Jean-François (De Gruyter, 2021)
To evaluate the efficacy of two decontamination protocols on cyclophosphamide surface contamination and to explore its lasting effect 30 days later.